Torsion experiment and cracking-torque formulae of hollow prestressed concrete beams. (1st October 2019) - Jeng, Chyuan-Hwan; Chao, Min; Chuang, Hui-Chun
Highlights: Ten hollow PC beam specimens under pure torsion were tested. An accurate measurement of small twists and prestressing forces was achieved. Testing of large specimens with high prestress and concrete strengths was enabled. Experimental results from the 10 specimens are presented. A new cracking-torque Tcr formula for hollow PC beams is proposed. Abstract: Torsion experiments involving prestressed concrete (PC) beams have had a number of limitations, and the literature has rarely examined hollow PC beam specimens. Following the advances in testing the torsion of solid PC beams, a new experimental project was conducted to test 10 hollow PC-beam specimens under pure torsion. This new torsion test of hollow PC beams achieved an accurate measurement of small twists before and around cracking. It also improved other aspects, such as providing a precise measurement of prestressing forces and prestress transfer. This test also enabled assessment of relatively large specimens with medium to high prestress levels and high concrete strengths. Experimental results from 10 specimens are presented in this paper. The experimental values of cracking torque Tcr for the 10 specimens are compared, with the Tcr values calculated using a recently developed rational formula for reinforced concrete. Using these comparisons, a new Tcr formula for thin- and thick-walled hollow PC beams is proposed, which accurately predicts the cracking torques of the 10 specimens.